2011
DOI: 10.1017/s1751731110001618
|View full text |Cite
|
Sign up to set email alerts
|

Online prediction of fatty acid profiles in crossbred Limousin and Aberdeen Angus beef cattle using near infrared reflectance spectroscopy

Abstract: The objective of this study was to examine the online use of near infrared reflectance (NIR) spectroscopy to estimate the concentration of individual and groups of fatty acids (FA) as well as intramuscular fat (IMF) in crossbred Aberdeen Angus (AA3) and Limousin (LIM3) cattle. This was achieved by direct application of a fibre-optic probe to the muscle immediately after exposing the meat surface in the abattoir at 48 h post mortem. Samples of M. longissimus thoracis from 88 AA3 and 106 LIM3 were scanned over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
26
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
9
26
0
2
Order By: Relevance
“…Results for IMF content from our study are consistent with those reported by Prieto et al (2006) and Ripoll et al (2008) on homogenized meat samples, whereas they are greater to those reported by Prieto et al (2011) who tested the ability of NIRS on intact meat samples in the abattoir. As reported by Prieto et al (2009), the sample preparation (in particular the homogeneity of meat samples) plays an important role in the accuracy of NIRS prediction; in fact, the chemical composition in minced samples can be more accurately predicted by NIRS than in intact tissue.…”
Section: Predictions Of Imf and Fa Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…Results for IMF content from our study are consistent with those reported by Prieto et al (2006) and Ripoll et al (2008) on homogenized meat samples, whereas they are greater to those reported by Prieto et al (2011) who tested the ability of NIRS on intact meat samples in the abattoir. As reported by Prieto et al (2009), the sample preparation (in particular the homogeneity of meat samples) plays an important role in the accuracy of NIRS prediction; in fact, the chemical composition in minced samples can be more accurately predicted by NIRS than in intact tissue.…”
Section: Predictions Of Imf and Fa Contentsupporting
confidence: 92%
“…Several studies have confirmed the ability of NIRS to predict the content of IMF in beef (Ripoll et al, 2008;Prieto et al, 2006Prieto et al, , 2011 using different NIRS system and meat treatments. Results for IMF content from our study are consistent with those reported by Prieto et al (2006) and Ripoll et al (2008) on homogenized meat samples, whereas they are greater to those reported by Prieto et al (2011) who tested the ability of NIRS on intact meat samples in the abattoir.…”
Section: Predictions Of Imf and Fa Contentmentioning
confidence: 90%
“…Nevertheless, no significant improvement was found compared with the use of untreated spectral data, in agreement with De Marchi et al (2011) and Cecchinato et al (2011). The previous procedures were done according to Williams (2001), Prieto et al (2011), andDe Marchi et al (2012).…”
Section: Chemometric Models For Data Analysissupporting
confidence: 84%
“…This was confirmed by Liu et al (2003) who found an absorption band produced by myoglobin oxidation at 760 nm. The band at 1193 was related to C-H bonds as confirmed by several authors (Murray & Williams, 1987;Prieto et al, 2011;. Bands at approximately 1450 nm are related to water absorption and usually these signals are stronger with respect to those of other components, so that water signals can hide signals related to components such as proteins, which are usually at 1485 nm.…”
Section: Spectra Variation and Informationsupporting
confidence: 53%
See 1 more Smart Citation